Efficiency and productivity analysis of construction companies in Libya / Abdullah Ahmad A. Eltaief - A. Eltaief, Abdullah Ahmad (2011)
The purpose of this study is to measure and investigate efficiency and productivity by using Data Envelopment Analysis technique (DEA) and Malmquist Total Factor Productivity (TFP) index for cross-section time series data involving 26 firms of Libyan construction firms over the period 1995-2005. A multiple input-output nonparametric model was used to measure technical, cost, revenue and profit efficiencies. Source of productivity growth was also investigated to identify for efficiency change or technology change of the firms under study. The input variables comprise assets, equity and numbers of employees, while the output variables are revenue and profit. This study also examines the impact of three moderating' variables - size, age and change of government policy (or deregulation) on the efficiency and productivity measures of the firms concerned. Change of government policy refers to Libya opening its doors to foreign companies to operate in its country beginning 2003. This study also conducts statistical test of significance for the overall results, in particular the Mann-Whitney's Test was used to test hypothesis for the moderating variables. The relationship between technical, cost, revenue and profit efficiency scores are also tested for their statistical significance before interpretation in the light of hypothesis of interest.